Derived proteins from cry genes of bacillus thuringiensis - Espinoza Esquivel, Ana Mercedes (2018)
Combinations of Bacillus thuringiensis (Bt) proteins and nucleic acids encoding these Bt proteins are disclosed. Plants transformed with nucleic acids encoding these Bt proteins are also disclosed